2017
DOI: 10.1007/s40519-017-0411-z
|View full text |Cite
|
Sign up to set email alerts
|

Factor structure and reliability of the Multidimensional Body–Self Relations Questionnaire in Chilean youth

Abstract: The aim of this study was to ascertain the psychometric properties of the Multidimensional Body-Self Relations Questionnaire (MBSRQ) for a sample of youth in Chile. Cross-sectional survey was conducted with 451 participants. A non-clinical sample of adolescents and young adults between 15 and 25 years responded the MBSRQ and a sociodemographic questionnaire. Factorial analysis identified seven factors and provided empirical evidence that supports the use of these factors to evaluate body perception in Chilean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 31 publications
0
2
0
1
Order By: Relevance
“…The validity of the main sections of the questionnaire was reviewed and verified by Brown, Cash and Mikulka (1990), and showed a reliability coefficient of 81% [35]. The Multidimensional Body-Self Relations Questionnaire is a standard questionnaire used in various studies [36][37][38][39]. According to previous studies, this questionnaire is acceptable in Iranian samples according to psychological fitness [40][41][42][43][44].…”
Section: Methodsmentioning
confidence: 99%
“…The validity of the main sections of the questionnaire was reviewed and verified by Brown, Cash and Mikulka (1990), and showed a reliability coefficient of 81% [35]. The Multidimensional Body-Self Relations Questionnaire is a standard questionnaire used in various studies [36][37][38][39]. According to previous studies, this questionnaire is acceptable in Iranian samples according to psychological fitness [40][41][42][43][44].…”
Section: Methodsmentioning
confidence: 99%
“…In the Chilean context, a study conducted with 451 participants between 15 and 25 years old evaluated, through exploratory factor analysis, the properties of the MBSRQ in a Chilean adolescent population, presenting sufficient internal consistency [57]. These findings confirmed that the MBSRQ factors have sufficient internal consistency to be used in research with the adolescent population in Chile.…”
Section: Introductionmentioning
confidence: 72%
“…Items from Ohanian's [30] scale for endorser credibility, along with items from Edell and Burke's [31] influence of endorsers scale, were adapted to determine if the manipulation was successful. To measure individual differences in the participants, items from Cruzat et al's [32] body satisfaction scale and Dweck's [28] implicit theories were employed. To measure the de-pendent variable, one item from Speed and Thompson's 2009 purchase intention scale was engaged.…”
Section: Methodsmentioning
confidence: 99%
“…The mockup endorsements for each influencer were followed by the succeeding measures (a) influencer familiarity; (b) intent to purchase [33]; (c) endorsers' perceived expertise, trustworthiness, and attractiveness [30]; and (d) feelings from the ad [31]. Following the evaluation of all three influencers, the participants completed a multidimensional body self-relations questionnaire [32] and an implicit theory of appearance scale [27]. Each of the scales were based on previous studies within the literature and were either presented on five-point Likert scales or semantic differential scales.…”
Section: Data Collection and Proceduresmentioning
confidence: 99%